CADMIUM INDUCED OXDATIVE STRESS IN HEPTAOCYTES OF SNAKEHEAD FISH CHANNA PUNCTATUS (BLOCH.)- A INVITRO STUDY - K.K. SHUKLA,; DIWAKAR RAM TRIPATHI,; ANURADHA SHUKLA,; J.P.SHUKLA, (International Journal of Pharma and Bio Sciences, 2013)
Present study has been undertaken to assess the toxicity of cadmium in vitro for viability of hepatocytes, lactate dehydrogenase leakage, glutathione and lipid peroxidation in Channa punctatus (Bloch), a freshwater snake head fish. Three concentrations of cadmium as cadmium chloride (0.1µg/ml; 3.0µg/ml and 5.0µg/ml) besides one control has been selected. Observations reveal that except lowest concentration of cadmium (0.10µg/l), the rest two concentration (3.0µg/ml and 5. 0µg/ml) exerted significant decline (P<0.05) in the viability of heptocytes, lactic dehydrogenase leakage and glutathione as compared to control. However, significant increase (P<0.05) was noticed in the lipid peroxidation in terms of MDA (Malon-di aldehyde) treated with 3.0µg/ml and 5.0µg/ml of cadmium chloride concentration as compared to control. Lowest concentration (1. 0µg/ml) of cadmium chloride could produce no significant alteration in lipid per oxidation. Causo-mechanism of these findings has been discussed in this paper.